APPLICATION OF MULTI-OBJECTIVE OPTIMIZATION BY RATIO ANALYSIS (MOORA) IN DETERMINING THE LOCATION OF BERKAH TIRTA'S DRINKING WATER BUSINESS - Abdul Rahman; Andreas Dwiyanto; Agus Iskandar (CV. Adiba Aisha Amira, 2025)
In the workplace environment, competition is a common phenomenon, especially when it comes to determining the location to start a business, namely the selection of the right location. The business of water refill stations is experiencing rapid development, and the success of this business is significantly influenced by the accurate determination of the location. To enhance efficiency in location determination, the MOORA method is employed an analytical tool for decision-making. The use of the MOORA method in this research aims to analyze and compare each potential location based on predetermined criteria such as accessibility, market potential, operational costs, space size, crowd center and other external factors. The implementation of MOORA is expected to serve as an initial step in making strategic decisions related to location determination in various fields of business and provide a foundation for further research to develop more advanced methods in location selection. The results of the MOORA implementation in determining the strategic location indicate that location D or alternative is the preferred choice with a value of 0.323517894.